2019
DOI: 10.15548/al-masraf.v4i2.268
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Effect of Service Quality on Satisfaction and Loyalty With Islamic Economic Approach (Study on BMT Members in Puskopsyah Jambi)

Abstract: This study aimed to determine the effect of service quality on satisfaction and loyalty of Baitul Maal Wa Tamwil (BMT) members who become members of the Sharia Cooperative Center (PUSKOPSYAH) in Jambi. The development of BMT in Jambi is quite slow compared to other provinces on the SumatraIsland; so this research was carried out in Jambi City. This research design used quantitative methods with a survey approach. The type of data used was primary data. Primary data were obtained through distributing questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…According to (Jochen Wirtz, 2014), loyalty is recently used in a business context to describe the willingness of customers to always use the company's products, especially executives, for the long term and to recommend the company's products to friends and colleagues. (Fitri et al, 2019) defines loyalty as a combination of happy customer attitudes (customers' favorable attitude) and repeat purchase behavior.…”
Section: Accordingmentioning
confidence: 99%
See 2 more Smart Citations
“…According to (Jochen Wirtz, 2014), loyalty is recently used in a business context to describe the willingness of customers to always use the company's products, especially executives, for the long term and to recommend the company's products to friends and colleagues. (Fitri et al, 2019) defines loyalty as a combination of happy customer attitudes (customers' favorable attitude) and repeat purchase behavior.…”
Section: Accordingmentioning
confidence: 99%
“…The results of this study were proven in a previous study conducted by (Tamher, et al 2019) regarding the Effect of Place on Consumer Satisfaction at the Bogor Collection Garden Restaurant, stating that the Store Atmosphere has a positive effect on consumer satisfaction. (Fitri et al, 2019) (Mulyana, 2019) about the Effect of Store Atmosphere, Product Quality, and Service Quality on Consumer Satisfaction at Artist Coffee Studio showed that the place had a significant effect and a positive value on consumer satisfaction.…”
Section: Research Findingmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet people's expectations for quality service, the dimensions of service quality as theoretical indicators can be explained as follows: Tangibility, Reliability, Responsiveness, Assurance, and Empathy. These indicators provide a framework for understanding and assessing service quality [31,32].…”
Section: Service Qualitymentioning
confidence: 99%
“…Customer satisfaction, according to Sharia, is a comparison between expectations with products or services that should be in accordance with Sharia and the accepted reality (Arfiana Burhan, Najib, and Endri 2021). According to Qardhawi, a product or service must see the company's performance related to the nature of honesty, trustworthiness, and truth as a guide to determine the level of satisfaction felt by consumers (Fitri, Ridhwan, and Hardiansyah 2019).…”
Section: A Introductionmentioning
confidence: 99%